Separation of Hexane-Benzene Mixtures by Emulsion Liquid Membrane. - A. Al Hemiri, Adil; D. Al Zaidi, Muhammad (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
The effect of operating parameters on the batch scale separation of hydrocarbon mixture (benzene and hexane) using emulsion liquid membrane technique is reported. Sparkleen detergent was used as surfactant and heavy mineral oil as solvent to receive the permeates. From the experimental results, the parameters that influenced the permeation are, composition of feed, contact time with solvent, ratio of volume of solvent to volume of hydrocarbon feed, ratio of volume of surfactant solution to volume of hydrocarbon feed, surfactant concentration, mixing intensity and glycerol as polar additive in the surfactant solution to eliminate drop breakup. The best conditions for the separation in this study were found to be: composition of feed (mole fraction of benzene=0.5245), contact time of 10min. , ratio of volumes of solvent to feed equal 3.5 , ratio of volumes of surfactant solution to feed of 0.4, surfactant concentration of 1wt%, mixing intensity equal 1000rpm and 70% by weight of polar additive. These conditions gave a separation factor of (8.0).